Radioactivity degree different deposits of bentonites - Agayeva Z.R.; Jabarov E.E.; Yagubov A.I.; Mehdiyeva R.N.; Farkhatova N.B.; Gasimova A.M. (Институт катализа и неорганической химии имени академика М. Нагиева Национальной Академии Наук Азербайджана, 2018)
There has been studied a degree of radiation activity of bentonite taken from deposits (Gizil Dere, Dash-salahli, Agdere and others), depending on the depth of bedding. It has been established that a degree of radioactivity bentonite rocks depends on the depth of bedding, but does not depend on amount of mont-morillonite..
Keywords: bentonites; radiation activity; montmorillonite